Eksplorasi Nilai Pendidikan Lingkungan Cerpen Daring Republika: Kajian Ekokritik - Juanda (Institut Teknologi Sepuluh Nopember, 2018)
The purpose of this study is to explore the value of environmental educationand interaction between characters and nature in the short stories of theRepublika newspaper. This type of research is a qualitative study bydescribing descriptive or qualitative descriptive data. The data source comesfrom the Republika Newspaper which can be accessed in https://lakonhidup.wordpress.com. The data focus on environmental phenomena inthe short story of the 2015 to 2018 edition of Republika newspaper. Thetechnique used is the content analysis technique. The data were analyzedusing an ecocritical approach Grag Garrard (2004). Based on the results ofthe research, it was concluded that the republika short story contained anenvironmental theme whose proportions were very lacking. The dominantenvironmental phenomenon highlights natural and forest disasters. The valueof Republika's short stories environmental education, namely: tree planting,reforestation of forests that have been exploited, the implementation of rulesand regulations for deforestation, and animal conservation.